The Correlation of Serum IL-12B Expression With Disease Activity in Patients With Inflammatory Bowel Disease. Issue 23 (June 2016) - Lee, Hye Won; Chung, Sook Hee; Moon, Chang Mo; Che, Xiumei; Kim, Seung Won; Park, Soo Jung; Hong, Sung Pil; Kim, Tae Il; Kim, Won Ho; Cheon, Jae Hee
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Genetic variants in IL12B, encoding the p40 subunit common in interleukin-12 (IL-12) and interleukin-23, were identified as the susceptibility loci for inflammatory bowel disease (IBD). This study aimed to identify the correlation of serum IL-12B expression with disease activity in patients with IBD and evaluate the possibility of IL-12B as a biomarker for assessing inflammatory status in IBD. A total of 102 patients with IBD, including 38, 32, and 32 patients with Crohn's disease (CD), ulcerative colitis (UC), and intestinal Behçet's disease (intestinal BD), respectively, were included. The clinical and laboratory data from the patients were collected at the time of serum IL-12B measurement. Serum IL-12B levels were measured using an enzyme-linked immunosorbent assay. The median IL-12B levels in patients with CD, UC, and intestinal BD were significantly higher than those in controls (1.87, 2.74, and 2.73 pg/mL, respectively, vs. 1.42 pg/mL, all P  <0.05). IL-12B concentrations were associated with disease activity in patients with UC and intestinal BD but not in those with CD. IL-12B levels were increased with increasing disease activity in patients with UC ( P  <0.001). Likewise, patients with active intestinal BD had higher IL-12B levels than those without active disease ( P = 0.008). IL-12B levels were correlated with the endoscopic disease activity of UC ( P = 0.002) and intestinal BD ( P = 0.001) but not that of CD. Serum IL-12B levels were significantly correlated with clinical and endoscopic disease activity in patients with UC and intestinal BD, suggesting its potential use as a biomarker for assessing disease activity in these patients.